"Not just right" experiences account for unique variance in eating pathology. Issue 5 (3rd September 2018) - Kennedy, Grace A.; McDermott, Katherine A.; Mathes, Brittany M.; Summers, Berta J.; Cougle, Jesse R.
ABSTRACT: "Not just right" experiences (NJREs) are uncomfortable sensations of incompleteness linked to obsessive–compulsive disorder; however, NJREs may be transdiagnostic and play a role in eating pathology. The current study examined relations between NJREs and eating pathology in undergraduate students. Participants ( n = 248) completed self-report and behavioral assessments. Controlling for obsessive–compulsive symptoms, negative affect, and perfectionism, NJRE frequency was associated with greater drive for thinness, body dissatisfaction, and bulimic symptoms. Discomfort in response to a visual in vivo NJRE task was positively associated with drive for thinness and body dissatisfaction. The present study provides initial evidence for NJREs in eating pathology. Theoretical implications are discussed.